Establishment Of The Fact Of Executing Handwritten Manuscripts And Notes With Unusual (Left) Hand - Bidniak, Hanna; Sokolenko, Liubov (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2022)
The research paper outlines principle issues arising in solution of identification and diagnostic tasks of forensic handwriting examination when performing handwritten manuscripts with left hand. De-automation of the writer’s writing skills is considered. Attention is drawn to factors that affect change in handwriting. On the basis of specialized literature and thorough analysis of forensic experts’ conclusions, common and individual features of handwriting and signatures inherent in left-hand writing have been singled out. Emphasis have been made on main tasks of forensic expert at the stages of research, in particular while preliminary research on manuscripts executed in unusual conditions. Peculiarities of evaluation of the set of identified features and formulation of conclusions with a different specificity level given overall decrease in the degree of proficiency in handwritings among population are emphasized
Keywords: unusual conditions; change in handwriting; left-hand writing skills; diagnostic tasks